Uma imersão no passado-presente: o revisionismo bolsonarista sobre a ditadura (2011-2019) - Batista, Ariel Cherxes (2020)
Between 1964 and 1985 arose the Military Dictatorship in Brazil. Unfolded by a civil-military coup d'etat against the acting president João Gulart on March 31st of 1964. Backed by the American government and organized by the armed forces along with sector